Multi Mycotoxins Analysis in Rice Using LC-MS/MS - Riswahyuli Riswahyuli; Loise RS; Niza Nemara (MPI (Media Pharmaceutica Indonesiana), 2016)
Multi mycotoxins analysis in this research has the purpose to develop method of analysisfor rice sample with a simple and fast preparation and novel technology using LC-MS/MS. Several blankrice samples were spiked with standards of 8 classes of mycotoxins (Aflatoxin B1, Aflatoxin B2, AflatoxinG1, Aflatoxin G2, Deoxynivalenol, Zearalenon, T-2, and HT-2). Parameter of linearity, precision, recovery,limit of detection and limit of quantification were obtained and calculated. The result shows that all thevalidation parameters comply with criteria of method validation. Sonication method that was chosen toextract analites and Solid Phase Extraction Column that used for sample clean up are successful methodsthat have contribution for precise and accurate data. The Identification and quantification with LC-MS/MS help to determine and distinguish each mycotoxin through chromatogram appearance, retention timeand a specific m/z.